IMPLICATURE OF THE UTTERANCES AT COURT: A PRAGMATICS STUDY - Arfian Hikmat Ramdan (English Journal Literacy Utama, 2020)
In everyday conversations, there have been found some non-observe to the principle of cooperation which result in different interpretations (implicature). It is a situation where the speaker wants to convey a meaning that is more than the word spoken. Conversational Implicature is intended for the hearer to understand what is said by the speaker; to interpret, to suggest or to explain something. The purpose of the research was to reveal the implicature of speech acts that occur in court in cases of murder of human rights activists. The result of the research is then analyzed with the aim of getting the expected findings. The method used in this study is descriptive qualitative. The data from the research are in the form of text of utterances in the court taken from the internet. The results of this research indicate that the implicature which indicated by evidence of a lie was 15 utterances or 16.8% from 89 utterances or 83.2%. The utterances that was produced included non-observe to one maxim; maxim of quality, non-observe to two maxim; maxim of quality and quantity, and non-observe to three maxim; maxim of manner, quantity, quality and maxim of manner, relevance, quality.